PARTISIPASI MASYARAKAT DALAM PENGELOLAAN EKOSISTEM MANGROVE TELUK JOR LOMBOK TIMUR - Samsul Hadi; Irwansah Irwansah; Muhammad Aminuddin (Jurnal Ilmiah Global Education, 2023)
The purpose of this study was to evaluate community participation in the management of the Jor Bay mangrove ecosystem in East Lombok. This research is a qualitative descriptive. This research was conducted in November 2022 in the area around the Jor Bay mangrove forest, Jerowaru District, East Lombok Regency. Data collection was carried out by distributing questionnaires, interviewing informants and direct observation. In particular, in this study, the focus on sampling of respondents was the residents of Pare Mas Village. The results of this study indicate that the community around the Jor Bay Mangrove Forest, especially the people of Pare Mas Village, have a real participation or role in the management of the Jor Bay mangrove forest.